TINGKAT PAPARAN KEBISINGAN AKTIVITAS PENERBANGAN PESAWAT UDARA PADA KAWASAN PEMUKIMAN PENDUDUK KELURAHAN TAFURE DAN TARAU KECAMATAN TERNATE UTARA - Rachman, Nurdiani; Robo, Tamrin; Adjam, Syarifuddin; Purwati, Endang (Jurnal GeoCivic, 2023)
The settlements in the Tafure sub-district and the Tarau sub-district are residential areas that are right around Sultan Babullah Airport with a residential distance from the airport of only about 1 (one) meter, this makes the people living in these areas always exposed to noise. This study aims to determine the noise level of aircraft activities in residential areas of Tafure and Tarau sub-districts, and to determine the role of environmental factors in the distribution of noise. The method used is descriptive quantitative where the data obtained is analyzed to determine the equivalent value of noise using the Leq (Equivalent Continous Noise Level) formula to see a comparison of noise levels from aircraft flight activities and make a percentage diagram. The results showed that the noise level in the Tafure sub-district during landing was 63.7 dB-75.3 dB and during take-off was 62.7 dB-74.1 dB. Whereas in the kelurahan, the noise level when the plane is landing is 63.8 dB-72.9 dB and during take-off is 65.9 dB-71.1 dB. The noise level in the two kelurahans has exceeded the noise threshold value set by KMLH No.48 of 2002, namely 55 dB for residential and residential areas. Factors that affect the noise level in the Tafure and Tarau sub-districts are caused by very minimal vegetation because the residential areas are already very dense and the wind speed in the two kelurahans is 0.98-1.31 m/s and for a temperature level of 71 .6% where the wind speed has no effect on the noise level.